Penerapan Kompres Lidah Buaya Dalam Menurunkan Derajat Feblitis Pada Anak Rawat Inap Di Rsud Pandan Arang Boyolali - Lady Ayu Febriana; Ida Nur Imamah; Panggah Widodo (STIKes Ibnu Sina Ajibarang, 2024)
Data according to the Ministry of Health of the Republic of Indonesia (2020) the incidence of phlebitis in 2020 reached 0.51%. Children are more at risk because children have different physical characteristics and attitudes than adults. From the results of observations and interviews with nurses of the Dadap Serep ward, it was found that the average child who experienced feblitis was children aged 2-6 years. To determine the results of the application of aloe vera compress in reducing the degree of feblitis in inpatients at Pandan Arang Boyolali Hospital. Descriptive research design with a case study approach conducted on 2 respondents and a pretest-posttest research design, the application was carried out 5 times for 20 minutes in two days. The results of the application after applying aloe vera compresses for 2 days were obtained for both respondents to experience a decrease in feblitis degree from the beginning of 2 to 0. There was a change in the degree of feblitis before and after the aloe vera compress from both .